Eksplorasi Kesalahan Siswa pada Materi Aljabar di SMP: Systematic Literature Review - Vivied Eka Pratiwi; Sampoerno, Pinta Deniyanti; Aziz, Tian Abdul (Pendidikan Matematika FKIP Universitas Mataram, 2025)
An educator must conduct error analysis to determine the extent to which students understand the lesson. Furthermore, student error analysis can also be used as evaluation material and as a consideration in subsequent learning. The purpose of this study was to review literature related to error analysis in junior high school algebra material. This research is a Systematic Literature Review. Data collection was conducted by reviewing articles that have the research topic of error analysis theory in junior high school algebra problems. Data collection came from journals indexed by Sinta for the past 5 years. The obtained articles were 16 articles that met the criteria. Based on the search results, it was found that the analysis theory frequently used to conduct error analysis in algebra material is the costalan theory with three indicators: conceptual errors, procedural errors, and technical errors. The types of errors that appear range from misinterpreting algebraic elements to misapplying correct concepts. Therefore, a possible solution is to create learning activities that emphasize active student involvement to help students understand the concepts of algebra